Acrylic acid composite emulsion coating and preparation method thereof
By leveraging the water-based system and specific components of acrylic composite emulsion coatings, the problems of high VOC emissions, poor weather resistance, and unsatisfactory film-forming properties of traditional coatings have been solved. This results in low VOC emissions, high weather resistance, and excellent film-forming properties, thereby improving the environmental friendliness and service life of the coatings.
Patent Information
- Application Number
- CN202511177686.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-21
- Publication Date
- 2025-10-28
AI Technical Summary
Traditional coatings suffer from high emissions of volatile organic compounds (VOCs), poor weather resistance, and poor film-forming properties, which affect their environmental friendliness and service life.
Acrylic composite emulsion coatings are used, which contain specific components such as acrylate monomers, functional monomers, protective colloids, emulsifiers, initiators and weathering agents. Through a water-based system and free radical polymerization process, a coating with low VOC emissions, high weather resistance and excellent film-forming properties is formed.
Significantly reduce VOC emissions, improve the weather resistance and film-forming properties of coatings, extend service life, and meet market demands for environmental protection and high performance.
Smart Images

Figure CN120842925A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of novel coating technology, specifically to an acrylic composite emulsion coating and its preparation method. Background Art
[0002] In the development of the coatings industry, as people's demand for environmentally friendly, durable, and high-performance materials continues to grow, the shortcomings of traditional coatings have gradually become apparent, making the research and development of new coatings an urgent priority. Traditional coatings, such as oil-based coatings, have many deficiencies in practical applications, seriously restricting the sustainable development of the coatings industry.
[0003] The emission of volatile organic compounds (VOCs) from traditional coatings is a particularly prominent issue. Oil-based coatings release large amounts of VOCs during the drying process, causing serious environmental pollution and posing significant health risks to workers and users. Long-term exposure may lead to respiratory illnesses, skin allergies, and even potential cancer risks. With increasingly stringent environmental regulations, reducing VOC emissions has become a critical issue that the coatings industry urgently needs to address.
[0004] In terms of performance, traditional coatings have poor weather resistance. Many coatings are prone to chalking, fading, and cracking under long-term exposure to environmental factors such as ultraviolet radiation, oxygen, and moisture. This lack of weather resistance is particularly pronounced in outdoor environments, significantly shortening the protective and decorative functions of the coating and increasing maintenance costs and frequency.
[0005] Furthermore, traditional coatings also have limitations in film-forming properties. Some coatings struggle to form a uniform, dense film in low-temperature or high-humidity environments, affecting the final performance and appearance quality of the coating. In certain special applications, such as high-humidity basements or industrial facilities with extreme temperature variations, these film-forming defects can lead to problems like coating peeling and flaking.
[0006] In today's increasingly environmentally conscious world, developing a new type of coating with low VOC, high weather resistance, and excellent film-forming properties has significant market value and application prospects. It can not only effectively meet people's pursuit of environmental protection and health, but also improve the service life and performance of coatings, reduce maintenance costs, open up new development directions for the coating industry, and promote technological progress and industrial upgrading throughout the industry. Summary of the Invention
[0007] The purpose of this invention is to address the problems of high volatile organic compound (VOC) emissions, poor weather resistance, and unsatisfactory film-forming properties in traditional coatings by providing a novel acrylic composite emulsion coating. This coating uses water as the dispersion medium and features low VOC emissions, high weather resistance, and excellent film-forming properties. It effectively improves the environmental friendliness and service life of coatings, meets market demand for high-performance environmentally friendly coatings, and promotes technological progress and sustainable development in the coatings industry.
[0008] To achieve the above objectives, the technical solution adopted by the present invention is: an acrylic composite emulsion coating, comprising the following components by weight: 30-50 parts of acrylate monomer mixture, 1-8 parts of functional monomer, 0.5-3 parts of protective colloid, 1.5-5 parts of emulsifier, 0.2-1.5 parts of initiator, 40-60 parts of deionized water, and 1-3 parts of weathering agent;
[0009] The weather-resistant agent is a compound represented by Formula 1:
[0010] Formula 1:
[0011] In Formula 1, Z1 is selected from any one of -C(=O), O, -C(H2), and -C(CH3)2.
[0012] Furthermore, the acrylate monomer mixture is selected from at least two of the following: methyl acrylate, ethyl acrylate, butyl acrylate, 2-ethylhexyl acrylate, and methyl methacrylate.
[0013] Furthermore, the functional monomer is selected from at least one of the following: acrylic acid, methacrylic acid, hydroxyethyl acrylate, hydroxypropyl acrylate, acrylamide, N-hydroxymethylacrylamide, and (meth)acrylate glycidyl ester.
[0014] Furthermore, the protective colloid is selected from at least one of polyvinyl alcohol or hydroxyethyl cellulose.
[0015] Furthermore, the emulsifier is selected from sodium dodecyl sulfate and / or sodium dodecylbenzenesulfonate.
[0016] Furthermore, the initiator is selected from: ammonium sulfate and / or potassium persulfate.
[0017] Furthermore, the weather-resistant agent is any one of the compounds shown in the following structures:
[0018]
[0019] A method for preparing an acrylic composite emulsion coating includes the following steps:
[0020] (1) Add the emulsifier, acrylate monomer mixture, functional monomer, weathering agent and 60% by weight of deionized water to a reaction vessel, mix, and shear emulsify to obtain a pre-emulsion;
[0021] (2) Dissolve the initiator in 20% by weight of deionized water to prepare an initiator solution;
[0022] (3) Add the protective colloid and 20% by weight of deionized water to the reactor, heat to 75-85°C, first add 10-15% of the total amount of the pre-emulsion and 20-30% of the total amount of the initiator solution, stir, and keep the reaction at the temperature for 15-30 minutes; then add the remaining pre-emulsion and initiator solution dropwise over 2-4 hours, maintaining the temperature at 80-85°C during the dropwise addition, stir and keep the temperature for 1-2 hours after the dropwise addition is completed, cool down to 60°C, stir for 0.5-1 hour, filter, and obtain an acrylic composite emulsion coating.
[0023] Furthermore, steps (1) and (3) are performed under a nitrogen atmosphere.
[0024] Furthermore, the shear emulsification temperature in step (1) is between 55-75°C.
[0025] Furthermore, an acrylic composite emulsion coating can be used in the surface coating of building energy-saving thermal insulation materials.
[0026] Furthermore, an acrylic composite emulsion coating is a type of curing coating.
[0027] The weather-resistant agent described in this invention has a molecular structure containing an imino active group (-NH), an aromatic ring conjugated structure, and a thiol group (-SH). The nitrogen atom of the amino group has a lone pair of electrons, which can efficiently capture free radicals generated during coating aging, reacting to form a stable nitrogen-centered free radical and interrupting the oxidation chain reaction. Under ultraviolet light or thermal stress, the imino group can form reversible hydrogen bonds with the carboxyl group of the polymer chain, dynamically repairing microcracks and maintaining the integrity of the coating. The conjugated π-electron system of the aromatic hydrocarbon can absorb 290-400nm ultraviolet light, converting light energy into harmless heat energy through energy level transitions. The aromatic ring disperses free radical energy through resonance delocalization, reducing reactivity. The thiol group (-SH) provides active hydrogen atoms, directly quenching free radicals; -SH can reduce ROOH to produce alcohols and stable thioethers, blocking the free radical initiation source; the sulfur atom chelates catalytic metal ions (such as Fe) in the coating. 2+ / Cu + This inhibits metal-catalyzed oxidation reactions. The actual impact on coating performance is: ① It reduces polymer main chain breakage and lowers the chalking rate; ② The aromatic ring structure inhibits chromophore photo-oxidation, resulting in ΔE ≤ 2.0 after 2400 hours of accelerated QUV aging.
[0028] The acrylic composite emulsion coating of the present invention achieves its synergistic mechanism through three core dimensions: significantly reducing VOC emissions, systematically improving weather resistance, and comprehensively optimizing film-forming performance. Its synergistic effect is specifically manifested as follows: The acrylate monomer mixture serves as the main polymer backbone, adjusting the glass transition temperature through a combination of at least two selected from methyl acrylate, ethyl acrylate, butyl acrylate, 2-ethylhexyl acrylate, and methyl methacrylate. This reduces VOCs (and decreases solvent requirements in aqueous systems) while providing an elastic and dense polymer chain structure, thereby optimizing film-forming performance under low-temperature and high-humidity conditions and supporting weather resistance. Functional monomers are introduced, with hydrophilic groups or crosslinking points selected from at least one of acrylic acid, methacrylic acid, hydroxyethyl acrylate, hydroxypropyl acrylate, acrylamide, N-hydroxymethylacrylamide, and glycidyl (meth)acrylate. These strengthen the polymer network through hydrogen bonds / covalent bonds, promoting rapid and uniform film formation (preventing detachment) and synergistically resisting UV chain breakage with weathering agents, indirectly reducing VOC emissions. The protective colloid uses polyvinyl alcohol or hydroxyethyl cellulose to stabilize the emulsion particles, ensuring film continuity and avoiding the use of organic stabilizers. The emulsifier is obtained through dodecyl sulfate... Sodium sulfate and / or sodium dodecylbenzenesulfonate form a stable oil-in-water pre-emulsion, achieving efficient monomer dispersion and laying the foundation for a smooth film surface, while inhibiting degradation caused by water vapor penetration. Ammonium sulfate and / or potassium persulfate are used as initiators to control free radical polymerization, forming polymers of moderate molecular weight to enhance film toughness and reduce residual monomers to delay coating aging. Deionized water serves as the core dispersion medium, directly eliminating organic solvent evaporation and ensuring uniform mixing of components during shear emulsification, allowing for rapid evaporation during film formation to create a dense structure. The core weather-resistant component is a compound of formula 1 containing imino (-NH), aromatic ring conjugated structures, and thiol groups (-SH). The imino group captures free radicals to interrupt the oxidation chain, the aromatic ring absorbs 290-400nm ultraviolet light and converts it into heat energy, and the thiol group quenches free radicals, reduces hydroperoxide (ROOH), and chelates metal ions. Through synergy with the polymer backbone and functional monomers, it maintains a color difference ΔE ≤ 2.0 after 2400 hours of accelerated QUV aging, achieving dynamic repair of microcracks and extending lifespan. All components are ultimately optimized for overall performance through emulsification and free radical polymerization processes, forming a synergistic system with water as the medium, low VOC emissions, high weather resistance, and stable film formation.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] 1. Significantly reduced VOC emissions: The coating of this invention adopts a water-based system with water as the dispersion medium, which reduces the use of organic solvents, thereby significantly reducing the emission of volatile organic compounds (VOCs) and making it more environmentally friendly.
[0031] 2. Systematically improve weather resistance: By adding weather-resistant agents with specific structures, free radicals can be effectively captured, oxidation chain reactions can be interrupted, and the weather resistance of the coating can be improved through multiple synergistic mechanisms, making it less prone to chalking, fading, cracking and other phenomena under the influence of environmental factors such as ultraviolet rays, oxygen, and water vapor.
[0032] 3. Comprehensive optimization of film-forming performance: The synergistic effect of each component optimizes the film-forming performance of the coating, enabling it to form a uniform and dense paint film even in low temperature or high humidity environments, thereby improving the protective and decorative functions of the coating and extending its service life. Attached Figure Description
[0033] Figure 1 This is the NMR spectrum of the weathering agent 1 described in this invention. Detailed Implementation
[0034] The technical solution of the present invention will now be clearly and completely described with reference to the accompanying drawings. Obviously, the described embodiments are merely some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0035] Preparation Example 1
[0036] Synthesis of weathering agent 1:
[0037]
[0038] Step 1: Under nitrogen protection, 15 g of starting material 1, 8.94 g of starting material 2, 10.40 g of sodium tert-butoxide, 1.49 g of tris(dibenzylacetone)dipalladium, 0.54 g of tri-tert-butylphosphine, and 200 ml of toluene were added to the reaction system. The mixture was heated to 110 °C and refluxed for 12 h. After the reaction was completed, the temperature was slightly lowered, and the mixture was filtered using diatomaceous earth. The filtrate was cooled to room temperature, washed three times with water, and the organic phase was retained. The aqueous phase was then extracted with ethyl acetate. The organic phases were combined, evaporated to dryness, and subjected to silica gel column chromatography using a mixture of petroleum ether and ethyl acetate as eluent to obtain 15.49 g of intermediate 1. Mass spectrometry (MS) [MS+1]: 517.
[0039] Step 2: Under nitrogen protection, 15.49 g of intermediate 1, 12.71 g of starting material 3, 23.82 g of potassium phosphate trihydrate, 0.06 g of pyridine-2-carboxylic acid, 0.42 g of CuI, and 200 mL of DMSO were added sequentially to the reaction system. The mixture was heated at 85 °C for 16 h. After cooling, the reaction mixture was extracted with ammonia solution and methyl tert-butyl ether. The organic phase was washed five times with water and then twice with saturated NaCl solution. Finally, the combined organic phase was dried with anhydrous magnesium sulfate, filtered, evaporated to dryness, and subjected to silica gel column chromatography using a mixture of petroleum ether and ethyl acetate as eluent to obtain 19.74 g of weathering agent 1. Mass spectrometry (MS) [MS+1]: 550.
[0040] Weathering agent 1 1 H NMR (Chloroform-d), Figure 1 : δ7.93-7.87(m,2H),7.86-7.78(m,4H),7.76-7.66(m,2H),7.45-7.37(m,2H),7.32-7.26(m,2H),7.12-7.0 5(m,2H),6.93-6.87(m,2H),4.60(m,1H),4.07(s,1H),3.12-2.81(m,9H),2.45(dd,3H),2.37-2.27(m,1H).
[0041] Preparation Examples 2-4
[0042] In Preparation Examples 2-4, weathering agent 2-weathering agent 4 were prepared sequentially, referring to the preparation method of Preparation Example 1, but replacing raw material 1. See Table 1 for details.
[0043] Table 1.
[0044]
[0045]
[0046] Example 1
[0047] Preparation of an acrylic composite emulsion coating:
[0048] 1. Components by weight of raw materials:
[0049] Acrylic monomer mixture: 40 parts, selected from a combination of butyl acrylate and methyl methacrylate in a ratio of 3:1. The butyl acrylate and methyl methacrylate were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.
[0050] Functional monomers: 4 parts, selected from a combination of acrylic acid and hydroxyethyl acrylate in a ratio of 1:1. Acrylic acid and hydroxyethyl acrylate were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.
[0051] Protective colloid: 1.5 parts, made of polyvinyl alcohol with a molecular weight of approximately 20,000. The polyvinyl alcohol was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.
[0052] Emulsifier: 3 parts, sodium dodecyl sulfate was selected and purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0053] Initiator: 0.8 parts, potassium persulfate was selected and purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.
[0054] Deionized water: 50 portions, prepared in the laboratory;
[0055] Weathering agent: 2 parts, using weathering agent 1 synthesized in Preparation Example 1.
[0056] 2. Preparation method:
[0057] (1) Add emulsifier (sodium dodecyl sulfate 3 parts), acrylate monomer mixture (40 parts), functional monomer (4 parts), weathering agent (2 parts), and 60% by weight of deionized water (i.e., 30 parts) to the reactor. Under a nitrogen atmosphere, heat to 65°C and shear emulsify at 2000 rpm for 30 minutes to form a uniform pre-emulsion;
[0058] (2) Dissolve the initiator (0.8 parts potassium persulfate) in 20% by mass of deionized water (i.e., 10 parts) in a beaker and stir until completely clear to prepare an initiator solution;
[0059] (3) Under a nitrogen atmosphere, a protective colloid (1.5 parts polyvinyl alcohol) and the remaining 20% by weight of deionized water (i.e., 10 parts) were added to another reactor, and the temperature was raised to 80°C. First, 12% of the total pre-emulsion and 25% of the total initiator solution were added, and the mixture was stirred at 300 rpm and kept at this temperature for 20 minutes to initiate seed polymerization. Subsequently, the remaining pre-emulsion and initiator solution were added dropwise over 3 hours, with the temperature maintained at 82°C during the dropwise addition to maintain polymerization activity. After the dropwise addition was complete, the mixture was stirred and kept at this temperature for 1.5 hours to ensure complete reaction. Then, the temperature was lowered to 60°C, and stirring was continued for 45 minutes. Finally, the mixture was filtered through an 80-mesh sieve to obtain a white emulsion-like acrylic composite emulsion coating.
[0060] Examples 2-4
[0061] An acrylic composite emulsion coating was prepared by referring to the preparation method of Example 1, except that the weathering agent was replaced sequentially with weathering agent 2-weathering agent 4 prepared in Preparation Examples 2-4, and the rest remained the same as in Example 1.
[0062] Comparative Example 1
[0063] An acrylic composite emulsion coating was prepared by referring to the preparation method of Example 1, except that the weathering agent was replaced with the antioxidant MMBI (CAS: 53988-10-6), and the rest remained the same as in Example 1.
[0064] Comparative Example 2
[0065] An acrylic composite emulsion coating was prepared by referring to the preparation method of Example 1, except that the weathering agent was replaced with antioxidant ODA (CAS: 101-67-7), and the rest remained the same as in Example 1.
[0066] Comparative Example 3
[0067] An acrylic composite emulsion coating was prepared by referring to the preparation method of Example 1, except that the weather-resistant agent was replaced with... Everything else remains the same as in Example 1.
[0068] Comparative Example 4
[0069] An acrylic composite emulsion coating was prepared according to the preparation method of Example 1, except that the weather-resistant agent was not added, and the rest remained the same as in Example 1.
[0070] Comparative Example 5
[0071] An acrylic composite emulsion coating was prepared according to the preparation method of Example 1, except that no functional monomers were added, and the rest remained the same as in Example 1.
[0072] Comparative Example 6
[0073] An acrylic composite emulsion coating was prepared according to the preparation method of Example 1, except that the protective colloid was not added, and the rest remained the same as in Example 1.
[0074] Performance testing:
[0075] Sample preparation: The surface of the tinplate substrate was cleaned to remove residual paint film, rust, oil, scale, and other debris, ensuring the substrate surface was free of rust, oil, dust, and watermarks. An acrylic composite emulsion coating prepared in the examples and comparative examples was applied to the clean tinplate surface to a thickness of 80 μm and dried at 80°C for 5 hours to obtain the test coating.
[0076] 1. Pencil hardness test: Hardness test was conducted according to GB / T6739-2006, and the data are shown in Table 2.
[0077] 2. Impact performance test: The impact performance test was conducted in accordance with GB / T20624.2-2006 standard, and the data are shown in Table 2.
[0078] 3. QUV Accelerated Aging Test: The sample was placed in a QUV ultraviolet aging chamber for accelerated aging testing. Cyclic conditions were set as follows: UVB-313 lamp irradiation (0.71W / m²). 2 The coating was subjected to aging processes including 80℃ for 8 hours and condensation (20℃ for 4 hours), for a total aging time of 2400 hours. After aging, the color change of the coating was measured using a spectrophotometer according to GB / T 7921-2008, and the Lab color was recorded. * The values were calculated and ΔE was determined. After aging, impact performance tests were conducted according to GB / T20624.2-2006 standard, and the loss rate was calculated. The data are shown in Table 2.
[0079] Table 2.
[0080] Pencil hardness Impact performance (cm) ΔE Impact performance loss rate (%) Example 1 5H 65 1.0 3 Example 2 5H 68 1.1 4 Example 3 5H 63 1.3 7 Example 4 5H 62 1.2 5 Comparative Example 1 5H 53 2.5 26 Comparative Example 2 5H 52 2.3 22 Comparative Example 3 5H 58 2.0 18 Comparative Example 4 4H 49 4.3 40 Comparative Example 5 2H 35 3.5 33 Comparative Example 6 H 28 3.8 38
[0081] The acrylic composite emulsion coating of the present invention has a pencil hardness of 5H, an impact performance between 62-68 cm, a ΔE between 1.0-1.3 after QUV accelerated aging, and an impact performance loss rate between 3%-7% after QUV accelerated aging.
[0082] The examples with the weathering agent of this invention showed significantly better overall performance than the comparative examples without the weathering agent or using alternative weathering agents. Regarding pencil hardness, the examples maintained a high hardness level, while the comparative examples showed a significant decrease in hardness when the weathering agent was absent or key components were missing. In terms of impact performance, the examples exhibited strong initial impact resistance with minimal loss after aging, while the comparative examples showed weaker initial impact resistance and a significantly increased loss rate after aging, indicating insufficient weather resistance. The color change (ΔE) trend showed that the examples exhibited minimal color change, indicating excellent UV resistance, while the comparative examples showed greater color change, reflecting deficiencies in weather resistance. Regarding the impact performance loss rate, the examples retained extremely high performance after aging, while the comparative examples showed a significantly increased loss rate, highlighting the lack of protective effect from the weathering agent. In summary, the weathering agent of this invention significantly improves the durability and stability of the coating through a synergistic mechanism, while the comparative examples without this system experienced a sharp decline in performance under accelerated aging conditions.
[0083] While embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions, and variations may be made to these embodiments without departing from the principles and spirit of the invention, and that the scope of the invention is defined by the appended claims and their equivalents.
Claims
1. An acrylic composite emulsion coating, characterized in that, It contains the following components by weight: 30-50 parts of acrylate monomer mixture, 1-8 parts of functional monomer, 0.5-3 parts of protective colloid, 1.5-5 parts of emulsifier, 0.2-1.5 parts of initiator, 40-60 parts of deionized water, and 1-3 parts of weathering agent; The weather-resistant agent is a compound represented by Formula 1: Formula 1: In Formula 1, Z1 is selected from any one of -C(=O), O, -C(H2), and -C(CH3)2.
2. The acrylic composite emulsion coating according to claim 1, characterized in that, The acrylate monomer mixture is selected from at least two of the following: methyl acrylate, ethyl acrylate, butyl acrylate, 2-ethylhexyl acrylate, and methyl methacrylate.
3. The acrylic composite emulsion coating according to claim 1, characterized in that, The functional monomer is selected from at least one of the following: acrylic acid, methacrylic acid, hydroxyethyl acrylate, hydroxypropyl acrylate, acrylamide, N-hydroxymethylacrylamide, and glycidyl (meth)acrylate.
4. An acrylic composite emulsion coating according to claim 1, characterized in that, The protective colloid is selected from at least one of polyvinyl alcohol or hydroxyethyl cellulose.
5. An acrylic composite emulsion coating according to claim 1, characterized in that, The emulsifier is selected from sodium dodecyl sulfate and / or sodium dodecylbenzene sulfonate.
6. An acrylic composite emulsion coating according to claim 1, characterized in that, The initiator is selected from: ammonium sulfate and / or potassium persulfate.
7. An acrylic composite emulsion coating according to claim 1, characterized in that, The weather-resistant agent is any one of the compounds shown in the following structures:
8. A method for preparing an acrylic composite emulsion coating according to any one of claims 1-7, characterized in that, The following steps are involved: (1) Add the emulsifier, acrylate monomer mixture, functional monomer, weathering agent and 60% by weight of deionized water to a reaction vessel, mix, and shear emulsify to obtain a pre-emulsion; (2) Dissolve the initiator in 20% by weight of deionized water to prepare an initiator solution; (3) Add the protective colloid and 20% by weight of deionized water to the reactor, heat to 75-85°C, first add 10-15% of the total amount of the pre-emulsion and 20-30% of the total amount of the initiator solution, stir, and keep the reaction at the temperature for 15-30 minutes; then add the remaining pre-emulsion and initiator solution dropwise over 2-4 hours, maintaining the temperature at 80-85°C during the dropwise addition, stir and keep the temperature for 1-2 hours after the dropwise addition is completed, cool down to 60°C, stir for 0.5-1 hour, filter, and obtain an acrylic composite emulsion coating.
9. The method for preparing an acrylic composite emulsion coating according to claim 8, characterized in that, Steps (1) and (3) are performed under a nitrogen atmosphere.
10. The method for preparing an acrylic composite emulsion coating according to claim 8, characterized in that, The shear emulsification temperature in step (1) is between 55-75°C.
Citation Information
Cited By
Coating weather-resistant agent, nano-composite anticorrosive coating and preparation methods of coating weather-resistant agent and nano-composite anticorrosive coating
CN121181463A
High-molecular green water-based paint for alpine regions and preparation process thereof
CN121249212A
Polymer green water-based paint for alpine region and preparation process thereof
CN121249212B